(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
In the human body, almost all processes occur in the presence of enzymes. The situation is no different with the work of the digestive tract. Digestive enzymes are macromolecular proteins. These are substances that allow complex compounds to be broken down into simpler forms. They are secreted in the gastrointestinal tract and take part in the digestion of various ingredients of consumed food. Digestive enzymes in the body are produced naturally by the digestive glands. And although each organ is responsible for its own enzyme, all compounds complement each other, and therefore it is so important that the body does not lack any of them. The digestion process begins in the oral cavity precisely due to the presence of salivary amylase produced by the salivary glands.